AB0284 HEMATOLOGICAL MARKERS OF SYSTEMIC INFLAMMATION CORRELATE WITH CLINICAL, LABORATORY AND ULTRASOUND DISEASE ACTIVITY PARAMETERS IN RHEUMATOID ARTHRITISPATIENTS. (June 2019) - Targonska-Stepniak, Bozena; Zwolak, Robert; Piotrowski, Mariusz; Majdan, Maria
Abstract : Background: An accurate measurement of disease activity and inflammation is essential for customizing the most appropriate management and treatment strategy in patient with rheumatoid arthritis (RA). Current data suggest that hematological markers of systemic inflammation [peripheral blood neutrophil-to-lymphocyte (NLR), platelet-to-lymphocyte (PLR) and monocyte-to-lymphocyte (MLR) ratios] could be used as novel, sensitive measures of inflammatory response, additionally to conventional laboratory and clinical markers [erythrocyte sedimentation rate (ESR), C-reative protein (CRP), Disease Activity Score of 28 joints (DAS28), tender joint count (TJC), swollen joint count (SJC)]. The ultrasonography US) of joints enables the disease activity assessment by quantifying thickening and vascularity of the synovium. Objectives: The goal of the study was to assess the relationship of NLR, PLR, MLR with the conventional disease activity markers (ESR, CRP, DAS28, TJC, SJC) and results of joints US, in patients with RA. Methods: The study was conducted in the consecutive 72 patients with RA (60 women, 12 men), with the mean (SD) age 53.4 (8.9) and disease duration 16.8 (10.3) years. The following procedures were assessed for all patients: joint counts, DAS28, complete blood cell counts, ESR, CRP, US of 24 small joints. Results: The mean (SD) values of hematological markers were as follows: NLR 3.24 (2.7) (range 0.2-13.96); PLR 193.26 (88.3) (range 71.2-560.8); MLR 0.3 (0.16) (range 0.06-0.87). The mean values of NLR and PLR were significantly lower in patients with low (DAS28 ≤3.2) vs moderate/high (DAS28 >3.2) disease activity; respectively NLR 2.4 (1.7) vs 4.0 (3.2), p=0.004; PLR 168.7 (58.0) vs 215.8 (104.9), p=0.4. Hematological markers of systemic inflammation were significantly, positively correlated with clinical, laboratory and US markers of the disease activity. Significant correlations were found between: NLR and DAS28, TJC, SJC, ESR, CRP, vascularity of synovium in US; PLR and DAS28, TJC, SJC, ESR, CRP, vascularity and hypertrophy of synovium in US; MLR and DAS28, SJC, ESR, CRP, vascularity and hypertrophy of synovium in US. In multiple regression test significant correlations were confirmed for: NLR and SJC (p=0.008), ESR (p<0.001), CRP (p<00.1), vascularity of synovium in US (p=0.02); PLR and ESR (p=0.03), CRP (p=0.03); MLR and DAS28 (p=0.04), ESR (p<0.001), hypertrophy of synovium in US (p=0.02). Conclusion: The results of the study suggest that hematological markers of systemic inflammation (NLR, PLR, MLR) may serve as reliable, inexpensive and effective measure of inflammation in RA. The strong association with US imaging is an attractive result because of its predictive value and usefulness in clinical practice Disclosure of Interests: Bozena Targonska-Stepniak Speakers bureau: Sandoz, Berlin-Chemie, Robert Zwolak: None declared, Mariusz Piotrowski: None declared, Maria Majdan Speakers bureau: MSD, UCB, Abbvie, Roche